ANALISIS KINERJA KEUANGAN PADA PT. PLN (Persero) PEMBANGKITAN SUMBAGUT SEKTOR PEMBANGKITAN PEKANBARU - Intan Nurafni; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to find out and analyze the performance of keuangan PT. PLN (Persero) Sumbagut Generation Pekanbaru Generation Sector period 2014-2018. Analysis method used based on KEPMEN BUMN Number: KEP-100 / MBU / 2002. Based on the results of analysis of financial performance data at PT. PLN (Persero) Generation SUMBAGUT Pekanbaru Generation Sector obtained the conclusion that the company’s financial performance is in poor conditon. (1) Analysis of Liquidity ratio with Cash ratio and Current Ratio shows that the company's financial performance is in poor condition. (2) Analysis of Solvency ratio with the ratio of total capital alone to total assets shows the company's financial performance is in good condition. (3) Profitability ratio analysis with ROE ratio and ROI of financial performance in fairly good condition (4) Activity ratio analysis with Collection Periodsindicator, Inventory Turnover and TATO, the Company is in excellent condition. Keywords : Analysis, Liquidity, Solvency, Profitability, Activity